Selection of organic matter as a wetland substrate for acid mine drainage treatment - Sekarjannah, Fitri Arum; Mansur, Irdika; Abidin, Zaenal; Fauzi, Anas Miftah (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
Acid mine drainage (AMD) is one of the problems arising from mining activities. Acid mine drainage is formed due to the oxidation of sulfide minerals such as pyrite (FeS2) by water and oxygen. Alternative management of AMD in a sustainable and eco-friendly way is constructed wetland. Therefore, this study was conducted to determine the type and composition of potential organic matter that can improve AMD quality. The study consisted of three stages: a screening of organic matter, a combination of two organic matters, and a combination of cow manure and empty fruit bunches (EFB) in various compositions. Types of organic matters used are cow, goat, and chicken manure, three types of compost, EFB, sawdust, wood chips, chopped water hyacinth, cocopeat, fresh waste and compost waste cajuputi leaf, waste of citronella distillation, baglog waste, and bagasse. The results showed that several types of organic matter could increase the pH of AMD. The combination of EFB and cow manure with a ratio of 2:1 is the best result because it can increase pH, reduce dissolved heavy metals and sulfates, and availability of raw materials that are abundant in nature, especially in Indonesia.